Pseudokeissleriella bambusicola gen. et sp. nov. (Lentitheciaceae, Pleosporales) from bamboos in Sichuan province, China - Yang, Yi; Zhang, Sheng-Nan; Yu, Xian-Dong; Liu, Jian-Kui (Phytotaxa, 2022)
During an investigation of ascomycetous fungi on bamboos in Sichuan province, China, a monotypic genus, Pseudokeissleriella, collected from dead culms of bamboos is introduced to accommodate P. bambusicola. Pseudokeissleriella bambusicola is characterized by having subglobose to globose, glabrous ascomata, and hyaline, septate, fusiform ascospores with subobtuse ends and a swollen upper cell, surrounded by a mucilaginous sheath with center depression. The phylogenetic analyses based on multi-gene matrix of SSU, ITS, LSU, tef-1α sequences showed that P. bambusicola presented a distinct lineage sister to Katumotoa and Neoophiosphaerella in Lentitheciaceae. The establishment of new taxa were justified by morphological and phylogenetic evidences. Morpho-phylogenetic differences between Pseudokeissleriella and some related genera Katumotoa, Keissleriella, and Neoophiosphaerella are discussed. Descriptions, illustrations, and notes for the new taxa are provided.